Analisis Kinerja Keuangan dengan Menggunakan Metode Du Pont System pada PT HM Sampoerna Tbk Periode 2020-2022 - Hasrul Hasrul; Agung Widhi Kurniawan; Romansyah Sahabuddin; Uhud Darmawan Natsir; Nurman Nurman (Jurnal Publikasi Manajemen Informatika, 2024)
The consumer goods industry, including the tobacco sector, plays a critical role in Indonesia's economy. Despite facing intense competition and regulatory challenges, this sector contributes significantly to national revenue through taxes and duties. Indonesia, with one of the highest smoking rates globally, saw substantial revenue from Tobacco Excise Duties (CHT), amounting to IDR 198.02 trillion in 2022. The COVID-19 pandemic exacerbated challenges by causing significant tax hikes, leading to reduced purchasing power and increased demand for illegal cigarettes. This study focuses on PT HM Sampoerna Tbk, a major player in the Indonesian tobacco industry, evaluating its financial performance using the Du Pont System for the years 2020-2022. The analysis reveals fluctuating Return On Equity (ROE), a declining Net Profit Margin (NPM), and Return On Assets (ROA), despite stable Total Assets Turnover (TATO) and Equity Multiplier (EM). The findings highlight the impact of external economic pressures and regulatory changes on the company's profitability and operational efficiency. This study provides insights into how financial performance metrics reflect the broader economic context and the effectiveness of management strategies.